Flow Characteristics and Experimental Verification of T-Groove Dry Gas Seal Under Different Flow States - Lanxia Zhang; Xuexing Ding; Shipeng Wang; Shuai Zhang (Lubricants)
With the improvement of dry gas seal efficiency in high-parameter fields, the flow pattern of gas film lubrication is complicated. Based on gas lubrication theory, the Reynolds equation of compressible gas was established with a bidirectional T-groove dry gas seal as the research object. The Reynolds equation was solved to obtain a modified turbulent film pressure distribution law that affects gas lubrication. The effectiveness of the calculation program was verified by experimental tests. The results show that with an increase in operating parameters, the turbulence effect caused the gas film pressure fluctuation in the T-groove region to intensify, resulting in gas film flow instability. In addition, the inertia effect improved, which slowed down the leakage and affected the change law of stiffness and the rigid leakage ratio. When the fluid speed and gas pressure were low, the inertia effect could be ignored. When the groove depth was increased to 8 μm, the height difference between the trough and non-T-groove region became larger due to the combination of the turbulence and inertia effects. Further, when the gas film thickness was 3 μm, the opening force and gas film stiffness were high due to the dynamic pressure effect in the small film thickness groove. An increase in the gas film thickness weakened the turbulence effect and reduced the gas film pressure fluctuation.